Breathability of running shoes - Tan, Keng Boon Augustine (2017)
An experimental study was carried out to investigate the features which contribute positively to the breathability of a pair of running shoes. Past literature was reviewed to research methods for testing and evaluating breathability. Modifications were made to the existing test jig and methodology used by the Institute for Sports Research (ISR). A wind tunnel test was carried out on five models of shoes with different conceptions of the upper and sole to quantify breathability by the mechanism of water vapor transmission. The mass of water loss is used to evaluate the breathability of a shoe, with a larger mass of water loss implying better water vapor transmission rate and better breathability. Wind tunnel tests indicated that shoes with a layer of mesh on the external surface of the upper have better breathability. Shoes with better breathability also tended to have higher heat loss, hinting at a relation between breathability and heat loss. Limitations within the experiment led to difficulties in identifying the specific features of the shoe construction which influence breathability by the vapor loss pathway. However, using the lessons learnt from this experimental study, developments were proposed for future investigations. Other potential areas of research were proposed to better evaluate breathability in future.